Structural and haemodynamic evaluation of less invasive surfactant administration during nasal intermittent positive pressure ventilation in surfactant-deficient newborn piglets. - Victoria Mielgo; Elena Gastiasoro; Fabrizio Salomone; Francesca Ricci; Miguel A Gomez-Solaetxe; Lara Olazar; Begoña Loureiro; Carmen Rey-Santano (PLoS ONE, 2023)
The most recent approaches to the initial treatment of respiratory distress syndrome (RDS)- involve non-invasive ventilation (NIV) and less-invasive surfactant (SF) administration (LISA). Combining these techniques has been proven a useful treatment option for SF-deficient neonates. The objective of this study was to explore the impact on the brain (using cerebral near infrared spectroscopy, NIRS) of different LISA methods during NIV, using nasal intermittent positive pressure ventilation (NIPPV) for treating neonatal RDS. For this, we used five groups of spontaneously breathing newborn piglets (n = 6/group) with bronchoalveolar lavage (BAL)-induced respiratory distress which received NIPPV only (controls), poractant-alfa using the INSURE-like method (bolus delivery) followed by NIPPV, or poractant-alfa using one of three LISA devices, 1) a nasogastric tube (NT), 2) a vascular catheter (VC) or 3) the LISAcath® catheter. We assessed pulmonary, hemodynamic and cerebral effects, and performed histological analysis of lung and brain tissue. Following BALs, the piglets developed severe RDS (pH<7.2, PaCO2>70 mmHg, PaO2<70 mmHg, dynamic compliance<0.5 ml/cmH2O/kg at FiO2 = 1). Poractant-alfa administration using different LISA techniques during NIPPV was well tolerated and efficacious in newborn piglets. In our study, although all groups showed normal physiological ranges of total lung injury score and biochemical lung analysis, VC and LISAcath® catheters were associated with better values of lung compliance and lower values of lung damage than NIPPV, NT or INSURE-like methods. Moreover, neither of the SF administration methods used (LISA or INSURE-like) had a significant impact on the histological neonatal brain injury score. Of note, the LISAcath® has been recently withdrawn from the market.